2020
DOI: 10.31616/asj.2019.0203
|View full text |Cite
|
Sign up to set email alerts
|

Does Combined Anterior-Posterior Approach Improve Outcomes Compared with Posterioronly Approach in Traumatic Thoracolumbar Burst Fractures?: A Systematic Review

Abstract: The aim of this systematic review was to evaluate the surgical, radiological, and functional outcomes of posterior-only versus combined anterior-posterior approaches in patients with traumatic thoracolumbar burst fractures. The ideal approach (anterior-only, posterior-only, or combined anterior-posterior) for the surgical management of thoracolumbar burst fracture remains controversial, with each approach having its advantages and disadvantages. A systematic review following the Preferred Reporting Items for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
0
26
1
9
Order By: Relevance
“…There seemed to be an inevitable difference in deciding a treatment. 24) There are some limitations in this study. First, the cohort of this study was heterogeneous, and analysis was difficult as the patients had different tumor types and prognoses, and thus in the follow-up period, the patients were managed by various treatment plans.…”
Section: Discussionmentioning
confidence: 91%
“…There seemed to be an inevitable difference in deciding a treatment. 24) There are some limitations in this study. First, the cohort of this study was heterogeneous, and analysis was difficult as the patients had different tumor types and prognoses, and thus in the follow-up period, the patients were managed by various treatment plans.…”
Section: Discussionmentioning
confidence: 91%
“…The combined approach have the benefits of both approaches and therefore allows: 1) direct debridement of the infectious focus, 2) better sagittal deformity correction, and 3) short-segment fixation which was least interfering to spinal motion (Fig. 4 ) [ 38 , 42 , 43 ]. It is notable that the short-segment fixation along with intervertebral fusion could offer as good outcome in the correction of lordosis and improvement of neurological function as long-segment fixation would, even if the vertebral bodies were eroded or destroyed [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors should be evaluated: the injury pattern, the presence of neurologic deficit, the patient’s medical condition, and the operator’s surgical skill [ 46 ]. Several studies have reported their use of MISS for the treatment of unstable thoracolumbar fracture with or without spinal cord injury; flexion- and extension-distraction injuries; and complex sacral fractures [ 46 - 49 ]. Although the necessity of spinal fusion for the treatment of spinal trauma is still controversial, fixation without fusion is considered to be effective in providing stability and sagittal balance for the treatment of thoracolumbar burst fractures without neurologic deficit.…”
Section: Minimally Invasive Spine Surgery For Complex Spine Pathologymentioning
confidence: 99%